Is preemptive analgesia a good choice for postoperative pain relief in lumbar spine surgeries?: A meta-analysis of randomized controlled trials. Issue 13 (2nd April 2021) - Zhang, Lu-kai; Li, Qiang; Quan, Ren-Fu; Liu, Jun-Sheng
Abstract: Background: Lumbar spine surgery is associated with moderate-to-severe postoperative pain. Adequate pain management during the postoperative period facilitates rehabilitation. Recently, preemptive analgesia has been considered among the important analgesic methods for reducing postoperative pain. However, its efficacy in postoperative pain relief after lumbar spine surgery remains unclear. This study aimed to evaluate the effects of preemptive analgesia on lumbar spine surgery. Methods: We searched for randomized controlled trials in PubMed (1996 to May 2020), Embase (1980 to May 2020), and Cochrane Library (CENTRAL, May 2020). We included seven studies that evaluated the preemptive analgesic efficacy in lumbar spine surgeries. Results: Seven studies, including 509 patients, met the inclusion criteria. Pooled data revealed that preemptive analgesia is effective for lumbar spine surgeries with respect to the visual analog scale score ( P < .05), total morphine equivalent consumption ( P < .05), and length of stay ( P < .05), without increasing complications ( P = .73). Conclusions: Our findings indicate that preemptive analgesia is safe and effective for lumbar spine surgery.